A unique RET EXON 11 (G691S) polymorphism in an Indian patient with a collision tumor of the thyroid - D'Cruz Anil K; Chaukar Devendra; Desouza Maria; Badhe Rakesh R; Rekhi Bharat; Arya Suprita; Kane S V (BMC, 2007)
Abstract Background Collision tumors of the thyroid are rare, with occasional reports dealing with their genetic analysis. Case presentation A 59 year old lady presented with a neck mass, associated with hoarseness of voice of 5 years duration. Radiological examination revealed nodular masses in the left lobe of her thyroid, along with one in the isthmus, extending into the right lobe and associated with enlarged neck nodes. FNAC from the left thyroid showed features of medullary carcinoma. On total thyroidectomy, 2 distinct tumor nodules were identified in the left lobe with another in the isthmus, showing features of medullary carcinoma (MTC), papillary carcinoma and follicular variant of papillary carcinoma, respectively, accompanied with nodal metastasis. Subsequently, she underwent radioablation. RET gene analysis of the patient, her 2 daughters and a grandson revealed a unique G691S polymorphism on Exon 11. Conclusion This unique case of a collision tumor of thyroid, including component of an MTC deals with the value of RET gene analysis and therapeutic implications in the index case and in family members.